THE APPLICATION OF TASK-BASED LEARNING (TBL) APPROACH TO IMPROVE STUDENTS’ ACADEMIC WRITING SKILL - Anna Stasya Prima Sari; Jontra Jusat Pangaribuan (Jurnal Education and Development, 2018)
In the context of English as a foreign language (EFL) and of English as a second language (ESL), writing might be a very hard language skill for learners to master. To succeed in writing, in presenting their ideas, the students need to equip themselves with at least a number of fundamental abilities such as how to create topic sentence, controlling idea, supporting sentences, concluding sentence, etc. This research was primarily conducted to improve students’ academic writing skill through the application of Task-Based Learning (TBL) approach and to find out the students’ responses after learning academic writing skill through the application of TBL approach. This research is Classroom Action Research (CAR) which was performed in two cycles. Each cycle consisted of four steps, namely planning, action, observation and reflection. There are 21 students as the subject of the research. The analysis of quantitative data showed that the students’ mean score increased continuously from 64,86 in the pretest, 74,71 in the posttest of cycle 1 to 86,14 in the posttest of cycle 2. The analysis of qualitative data showed that the application of TBL approach could increase the students’ interest, motivation and involvement in the academic writing classes. It is advisable that teachers or lecturers of English language should try applying TBL approach as one of approaches in order to improve their students’ academic writing skill.